A voyage with Hitchcock - Pomerance, Murray, 1946- (Albany : SUNY Press, 2021)
"Extensive meditations on the theme of the voyage in six Hitchcock films: Psycho, The 39 Steps, The Birds, Dial M for Murder, Rich and Strange, and Suspicion"--
Intro -- Contents -- Acknowledgments -- Introduction: Where We Go from Here -- 1. Whither Thou Goest: Psycho, Metamorphosis, Mother -- The Water Runs -- The Chain of Chances -- The Sound of Silence -- Boy's Best Friend -- Interlude: A Hand Job -- Hard Ware -- Three Journeys of Psycho -- [A] To and From the Past -- [B] Place -- [C] Profane -- 2. "God made the country": Remember The 39 Steps -- A Living Encyclopedia -- Steps -- In a Croft -- Memories -- The Union -- Unresolved -- 3. "Where do you come from?": Hitchcock's Winged Victory -- Apocalypse -- Interlude: 'Ologies -- New World -- Idée fixe -- I Remember Mama -- Traum(a) -- Lacunae -- In the Country -- Things Fall Apart -- Ep ilogue -- 4. Say Nice Things or Dial M for Murder -- Interlude: A Room with a View -- The Wrong Fugue -- Tennis Wrist -- Best Laid Plans -- A Chain of Rings -- Motive and Motif -- The Fire That Purifies -- Flawless -- Talking Points, or Points Talking -- Once Upon a Time -- A Feinting Spell -- 5. Rich and Strange: To the End of the World and Back Again -- Compass -- Into the Sun -- L'Invitation au voyage -- The Sun Will Come Out Tomorrow -- To the Far Away -- Itinerary -- A Hitchcockian Passport -- Class -- Mystery -- Destinations -- 6. Legal Tender: Suspicion, Passion, Perplexity -- On the Rails -- Blithe Spirit -- Chance -- The Knot -- Tangmere Tangles -- Cary Grant's Grant -- Eccentricities -- All the News That Fits -- Mystery -- Diffident -- Innocent Men -- Riddle -- Three Paths to Happ enstance -- Left Behind -- Doubt -- Milk -- A Cinematic Gesture -- Notes -- Works Cited -- Index.
Formerly CIP.
Includes bibliographical references and index.
Print version record.
JSTOR
Keywords: Hitchcock, Alfred, -- 1899-1980 -- Criticism and interpretation; Hitchcock, Alfred, -- 1899-1980; Travel in motion pictures; Thrillers (Motion pictures) -- History and criticism; Voyage au cinéma.; Thrillers (Films) -- Histoire et critique; PERFORMING ARTS / Film / History & Criticism; Thrillers (Motion pictures); Travel in motion pictures; Criticism, interpretation, etc